2018
DOI: 10.1007/s13238-018-0505-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-23-induced macrophage polarization and its pathological roles in mice with imiquimod-induced psoriasis

Abstract: Macrophages acquire distinct phenotypes during tissue stress and inflammatory responses. Macrophages are roughly categorized into two different subsets named inflammatory M1 and anti-inflammatory M2 macrophages. We herein identified a unique pathogenic macrophage subpopulation driven by IL-23 with a distinct gene expression profile including defined types of cytokines. The freshly isolated resting mouse peritoneal macrophages were stimulated with different cytokines in vitro, the expression of cytokines and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 46 publications
6
79
0
1
Order By: Relevance
“…It has been proved that IMQ-induced psoriasis-like skin inflammation is a typical disease associated with IL-23/IL-17 axis imbalance ( 54 , 55 ). Upregulated IL-23 and IL-17 have been found in both psoriatic patients ( 56 ) and psoriasis-like mice ( 57 ). IL-23 activates Th17 cells through STAT3 pathway, thus producing Th17-related cytokines, such as IL-17, IL-22, and TNF-α ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that IMQ-induced psoriasis-like skin inflammation is a typical disease associated with IL-23/IL-17 axis imbalance ( 54 , 55 ). Upregulated IL-23 and IL-17 have been found in both psoriatic patients ( 56 ) and psoriasis-like mice ( 57 ). IL-23 activates Th17 cells through STAT3 pathway, thus producing Th17-related cytokines, such as IL-17, IL-22, and TNF-α ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the differentiation of macrophages from HPCs under modeled microgravity or normal gravity conditions, we applied either IFN-γ and LPS or IL-4 to stimulate M1 and M2 polarization, respectively, as reported previously. 25,26 The results showed that both M1 and M2 polarization were significantly impaired in macrophages that were differentiated under modeled microgravity (Fig. 2).…”
Section: Spaceflight and Simulated Microgravity Significantly Inhibitmentioning
confidence: 93%
“…Alternatively, CD163+ macrophages were also shown to harbor this effector function. However, the in vivo distinction of a rather DC-like state versus a macrophage-like state is nontrivial, and the role of Tip-DCs/macrophages is under debate [70,71]. Although a single prominent cell type might be responsible for a certain cytokine response in a specific disease state, the cytokine milieu is sustained by various contributors (e.g., Langerhans cells, inflammatory dendritic cells, and mast cells [72][73][74]).…”
Section: Psoriasismentioning
confidence: 99%